The role of Pay-for-Success mechanisms within capital markets for social change in France and the U.S. - Chamberlin, Alexandra M. (Tufts Archival Research Center, 2018)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: Pay-for-success mechanisms have existed since the 1980s. Over the last decade, they have regained attention through the launch of the specific Social Impact Bond contracts. This paper aims to describe the role that Pay-for-Success (PFS) contracts, considered as both social innovations and financial instruments, play and could play within capital markets for social change in France and the US. It first introduces and compares the similarities and differences in the French and US ecosystems. Then, considering PFS contracts as social innovation tools, I discuss whether PFS are legitimate instruments to be financed in capital markets for social change based on the claims that they increase the availability of capital for social programs and improve their efficiency and effectiveness. Having nuanced the social justification for PFS, I then consider them as financial products and place them within three distinct capital markets for social change. The analysis shows promises for PFS contracts in the public spending and philanthropic spaces, with an opportunity to influence mainstream capital markets.